Photometric Observations and Light Curve Analysis of BL Eridani - Wonyong Han; Hong-Suh Yim; Chung-Uk Lee; Jae-Hyuck Youn; Joh-Na Yoon; Ho-Il Kim; Hong-Kyu Moon; Yong-Ik Byun; Sunyoup Park (Journal of Astronomy and Space Sciences, 2006)
We present light curves of a short period binary system BL Eridani. The light curves were observed with {it VRI} filters by a 50cm wide field robotic telescope at Siding Spring Observatory (SSO), equipped with a 2K CCD camera, which was developed by Korea Astronomy and Space Science Institute (KASI), and Yonsei University Observatory (YUO). The photometric observations were made on 6 nights by automatic operation mode and remote observation mode at SSO and KASI in Korea, respectively. We obtained new {it VRI} CCD light curves and new 5 times of minima, and analyzed the light curves with the Wilson & Deviney (1971) binary 2005 version and derived the new photometric solutions. The mass ratio q = 0.48 in this study shows different value with earlier investigators. According to the model analysis, it is considered that the BL Eri system is currently undergoing contact stage of the two binary components, rather than near-contact stage.